2008
DOI: 10.1016/j.nuclphysa.2008.03.003
|View full text |Cite
|
Sign up to set email alerts
|

How the Pauli principle governs the decay of three-cluster systems

Abstract: New approach to the problem of multichannel continuum spectrum of three-cluster systems composed of an s-cluster and two neutrons is suggested based on the discrete representation of a complete basis of allowed states of the multiparticle harmonic oscillator. The structure of the eigenfunctions and behavior of the eigenvalues of the three-cluster norm kernel are analyzed. Classification of the eigenvalues of the three-cluster systems with the help of eigenvalues of the two-body subsystem is suggested. Asymptot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…We first established this phenomenon in [4]. Only the fact that some eigenvalues for the three-cluster systems coincided with the eigenvalues for the binary subsystems was indicated previously.…”
Section: Allowed States Of the Systemmentioning
confidence: 66%
See 4 more Smart Citations
“…We first established this phenomenon in [4]. Only the fact that some eigenvalues for the three-cluster systems coincided with the eigenvalues for the binary subsystems was indicated previously.…”
Section: Allowed States Of the Systemmentioning
confidence: 66%
“…We include only those families that are characterized by odd values of the additional quantum number k, since, in [4], we showed that the addition of branches belonging to the families that are characterized by even values of k has virtually no effect on the energy or on the wave functions for 5 H continuum states. Here, we adopt the single-channel approximation and assume that the asymptotic behavior of the coefficients in the expansion of the 5 H wave function in allowed states is determined by expression (5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations